2013
DOI: 10.1080/13607863.2012.696577
|View full text |Cite
|
Sign up to set email alerts
|

Older adult problem drinkers: Who presents for alcohol treatment?

Abstract: The older adults assessed for alcohol treatment were drinking in amounts comparable to the treatment population of younger adult problem drinkers, men more so than women. The majority were not reporting problems with their drinking until they were on average in their middle-to-late 50s and were therefore considered to be late onset 'reactors' rather than early onset 'survivors' of longer term heavy drinking patterns reported in earlier studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 22 publications
1
13
0
15
Order By: Relevance
“…They concluded that although late-onset drinkers in general had experienced a higher frequency of life events related to overall problem drinking, there was no significant relation in this specific subcategory. Christie, Bamber, Powell, Arrindell, and Pant (2013) confirmed the tendency that married and cohabitating individuals seem to have greater alcohol consumption than those who are divorced, single, widowed, or separated. They too, however, failed to test whether the tendency was statistically significant.…”
Section: Associations Between Death Of Spouse and Late-onset Aud Or Hsupporting
confidence: 62%
“…They concluded that although late-onset drinkers in general had experienced a higher frequency of life events related to overall problem drinking, there was no significant relation in this specific subcategory. Christie, Bamber, Powell, Arrindell, and Pant (2013) confirmed the tendency that married and cohabitating individuals seem to have greater alcohol consumption than those who are divorced, single, widowed, or separated. They too, however, failed to test whether the tendency was statistically significant.…”
Section: Associations Between Death Of Spouse and Late-onset Aud Or Hsupporting
confidence: 62%
“…Nacionalni inštitut za zlorabo alkohola in alkoholizem (National Institute on Alcohol Abuse and Alcoholism -NIAAA) v Združenih državah Amerike opozarja na meje manjšega tveganja pri uživanju alkohola po 65. letu: največ 1 merica dnevno (ameriška merica je 14 g alkohola) in ne več kot 7 meric tedensko (Ryou, et al, 2012;Christie, et al, 2013). Upoštevati je treba, da je meja manj tveganega uživanja alkohola odvisna poleg od starosti tudi od spola in zdravstvenega stanja.…”
Section: Uvodunclassified
“…Druga kategorija uživalcev s poznim začetkom problematičnega uživanja alkohola okoli 50. leta ima običajno krajša in daljša obdobja abstinence in predstavlja tretjino problematičnih uživalcev, ki razvijejo uživanje alkohola kot odgovor na življenjske krize, kot so upokojitev, izguba drage osebe in občutki osamljenosti (Stanojević-Jerković, et al, 2011). V tretji kategoriji so uživalci, za katere je značilno kompulzivno uživanje alkohola z menjavanjem epizod ekscesnega uživanja alkohola in občasnih epizod kontroliranega uživanja in abstinence (Christie, 2013). Izidi zdravljenja odvisnosti od alkohola s poznim začetkom kažejo zelo dobre rezultate (Stanojević-Jerković, et al, 2011;Christie, et al, 2013;Andersen, et al, 2015;Isted, et al, 2015).…”
Section: Uvodunclassified
See 2 more Smart Citations